THE METHOD OF HYPNO-CIRCUMCISION IN KLINIK KHITAN PLUS HYPNOSIS IN PABUWARAN PURWOKERTO UTARA SUBDISTRICT - Abdul Mujib (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2016)
This research explains the method of hypno-circumcision in the clinic. Generally, the service of circumcision still uses a conventional method and less of attention toward the psychological side. Whereas, this factor is very important on how affecting the patients view’s toward circumcision. The main goal of this research is to know the implementation of hypnosis in medical field, especially circumcision process in Klinik Khitan Plus Hypnosis Pabuwaran.The method used in this research is descriptive-analysis. This method is used to provide an overview of the method of hypno-circumcision in Klinik Khitan Plus Hypnosis. This research found that method of hypno-circumcision in Klinik Khitan Plus Hypnosis is similar with hypnosis in general. The method of hypno-circumcision into four stages: preparation stage, induction stage, suggestion stage and termination stage. Preparation of hypno-circumcision in Klinik Khitan Plus Hypnosis begins from consultation to Ms. Novi as receptionist. Then, Induction is a main way to bring someone from conscious to subconscious mind. Giving suggestion is the core stage in the process of hypno-circumcision. Last stage is termination which defines as a gradual step to bring the subject to consciousness.